Training strategy for development of life insurance agent in facing the generation z market - Arneldy, Suryani; Sukamdani, Nugroho B.; Maharani, Maya Dewi Diyah (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
The purpose of this research is to reduce the gap between Life Insurance Agents who are mostly Generation X with the future market of Generation Z and the purpose of this research is Formulating the right Life Insurance Agent development strategy to be applied to Generation Z market penetration. The research method used is descriptive research with a qualitative approach. The population sample used in this study amounted to 5 people and for data analysis using ISM, SWOT and descriptive analysis. The results of this study are (1) This strategy is applied based on the utilization of existing strengths and opportunities. Training for Life Insurance Agents is carried out regularly and in a structured manner, enabling Life Insurance Agents to adapt to any changes that occur by applying technology to the life insurance business process. The application of technology will make it easier for companies to design more diverse products and keep up with the times. (2) The Program (Professional Development Program) is analyzed using ISM (Interpretative Structural Modeling) Analysis to find key sub-elements of each element of Program Objectives, Program Needs, Program Constraints, and Possible Changes that play a role in driving program success or vice versa. cause the program to fail. (3) One of the activities to realize the program is training.